Association between food choices motivators and physical activity in body image (dis) satisfaction in Portuguese adolescents - Sousa, Pedro Miguel Lopes de (2021)
Concerns about weight and body image are common among adolescents since they are particularly vulnerable to body-image dissatisfaction due to the normal physiological, social, and psychological changes they are going through. This study aims to analyse the relationship between food choice motivations and physical activity in the body-image perception among adolescents. Twelve to sixteen years old adolescents were recruited from three school districts. The Portuguese version of the Food Choices Questionnaire (FCQ) was used to assess food choice motivators, and the Quantification de l'Activité Physique en Altitude Chez les Enfants was used to assess physical activity and to calculate daily energy expenditure (DEE). Body image perception was measured using the Collins' sequence of seven silhouettes. Body image (dis)satisfaction was estimated by the present body shape minus the desired body shape. ANOVA and Kruskal-Wallis tests were performed to compare groups, and the post hoc Bonferroni test was used to compare target groups. A multinominal logistic regression was performed to analyse the association between gender, age, hours of sport's competition, FCQ and body dissatisfaction. All analyses were performed in IBM SPSS Statistics 26.0. The sample comprised 286 adolescents (51.4% females). Means of FCQ categories varied between 0.33 and 0.97 (range: -2 to 2). Regarding the categories of FCQ, statistically significant differences were found in the category of body satisfaction and weight control among the three groups (p=0.004). A preventive effect was found of choosing food regarding body satisfaction and weight control, on the body-image dissatisfaction.